An investigation of factors affecting quality of life in parents of chronically disabled children (Annals of Medical Research, 2022)
Aim: The study's first objective is to compare differences between fathers and mothers with and without chronically disabled children. The study's second objective is to analyze factors influencing the quality of life of mothers and fathers with chronically disabled children comprehensively.Materials and Methods: One hundred sixty parents, 48 mothers and 22 fathers with chronically disabled children, 45 mothers and 45 fathers without chronically disabled children, participated in the research. Data collection was performed by employing the Nottingham Health Profile (NHP), Beck Depression Inventory (BDI), Parenting Stress Index (PSI), Fatigue Severity Scale, Headache Impact Test (HIT), and Pittsburgh Sleep Quality Index (PSQI).Results: The childcare-related workload, HIT, NHP, BDI, and PSQI values of the mothers in the study group and BDI and PSQI values of the mothers in the control group were significantly higher than the values obtained by the fathers (p